Kemampuan Pemecahan Masalah Matematis Siswa SMP pada Materi Bangun Ruang - Harry Dwi Putra; Nazmy Fathia Thahiram; Mentari Ganiati; Dede Nuryana (Universitas PGRI Madiun, 2018)
This study aims to analyze students 'mathematical problem-solving abilities in solving the problem of build space and knowing students' opinions on mathematics. The study was conducted on grade VII students at one of SMPN in Cimahi. The research approach used is qualitative with descriptive method. Instruments have been validated and consist of problem-solving test, interview guides, and questionnaires. The test that students do is given a score and an analysis of error answers. Questionnaires are used to obtain information about students' opinions in solving problems. The results showed that as many as 5 students made comprehensions error, as many as 13 students made transformation error, as many as 29 students made process skill error, and as many as 33 students made encoding error, so it can be concluded that the problem-solving ability of students in one of SMPN in Cimahi is still low so it is necessary to do improvement effort. However, students have a positive opinion on mathematics with an average of 69.41%.